ANALISIS KOROSI PADUAN ZIRLO-Mo DALAM MEDIA NaCl MENGGUNAKAN METODE POLARISASI - Ajiriyanto, Maman Kartaman; Anggraini, Dian; Kriswarini, Rosika (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Zirlo-Mo is a zirconium type of alloy, which is developed as cladding material for light water reactor. As cladding material, the important parameter to be characterized is its corrosion resistance properties. The goal of this research is to study the corrosion resistance of zirlo-Mo in NaCl medium with varied concentration of 0.03; 0.3; and 3 % and compare it to the those of zircaloy-2 dan zircaloy-4 in the same medium. Samples were mounted into disk form and metallographically prepared, i.e. treatment with abrasive paper of 500 to 1200 grit SiC. The analysis of zirlo-Mo corrosion rate was performed by polarization method with a potentiostat. The advantage of this polarization resistance method is that it takes shorter testing time if compared to weight gain method, and it can be applied to analysis at low corrosion rate of below 0.1 mpy. Other tests were also done to support the corrosion rate analysis such as microhardness test with microhardness tester and microstructure examination with optical microscope. The tests results show that in general zirlo-Mo, zircaloy-2 and zircaloy-4 possess very low corrossion rate, i.e. below 1 mpy. The corrosion rate of zircaloy-2, zircaloy-4 and zirlo-Mo in NaCl 3 % medium are 0.006; 0.007 and 0.590 mpy respectively. The corrosion rate of zirlo-Mo is relatively the highest due to its lath martensite or accicular structure, which has high hardness value. The lath martensite structure and high hardness properties make zirlo-Mo highly susceptible to corrosion. Hardness test results show that the hardness value of zircaloy-2, zircaloy-4 and zirlo-Mo are 194.79; 227.95 and 360.05 HV respectively. The existence of solid solution of Mo and Zr-α as well as the martensite or acicular structure of zirlo-Mo result in high hardness value of the alloy.